630. Emergence of Colistin Resistance in the OVERCOME Trial: Impact of Combination Therapy with Meropenem. (4th December 2021) - Pogue, Jason M; Rybak, Michael J; Stamper, Kyle; Marchaim, Dror; Thamlikitkul, Visanu; Carmeli, Yehuda; Chiu, Cheng; Daikos, Georgios L; Dhar, Sorabh; Mangoni, Emanuele Durante; Gikas, Achilleas; Kotanidou, Anastasia; et al.
Abstract: Background: Colistin (COL) remains an important therapeutic option for carbapenem-resistant (CR) Gram-negative bacilli (GNB). COL is often utilized in combination with meropenem (MEM), in part due to concerns regarding the development of COL resistance with monotherapy. We recently completed a randomized controlled trial comparing outcomes in patients receiving COL + placebo to those receiving COL + MEM; herein we present data on the emergence of COL resistance in this trial. Methods: OVERCOME was an international, multicenter, randomized, double-blind, placebo-controlled study comparing COL and COL + MEM for the treatment of bloodstream infection and/or pneumonia due to CR GNB. Subjects were included in the modified intent to treat population (mITT) if their enrollment pathogen had a COL MIC ≤2 mg/L, as determined by broth microdilution (BMD). Daily blood and/or respiratory samples were obtained in patients per protocol until two consecutive negatives were obtained or the end of study treatment. All subsequent isolates were evaluated for COL resistance via BMD, defined as MIC ≥ 4 mg/L. Results: Of the 425 patients in the mITT population, 380 (191 COL; 189 COL + MEM) were evaluable for the endpoint of COL resistance development. The median age of the cohort was 70, 38% were female, 47% were white, and 45% were Asian. 70% had an index infection of pneumonia, 68% were in the intensive care unit at the onset of their infection, and A. baumannii was the most common pathogen (78% of patients). Baseline characteristics, infection type, severity of illness, and index pathogen were similar amongst treatment arms. No significant difference in resistance development was seen between the COL and COL + MEM groups overall (12% vs. 8%; p = 0.31), or in any subgroup (Table). In patients with A. baumannii, there was a trend towards decreased resistance development with COL + MEM (13.3% vs 7.5%; p = 0.13). Conclusion: We were unable to identify a significant difference in resistance emergence between treatment arms, but given the low incidence of this outcome, were underpowered to do so. The impact of COL + MEM on preventing emergence of COL resistance in A. baumannii warrants further clinical study. Disclosures: Jason M Pogue, PharmD, BCPS, BCIDP, Merck (Consultant)QPex (Consultant)Shionogi (Consultant)Utility Therapeutics (Consultant)VenatoRX (Consultant) Michael J. Rybak, PharmD, MPH, PhD, Paratek Pharmaceuticals (Research Grant or Support) Emmanuel Roilides, MD, PhD, FIDSA, FAAM, FESCMID, Merck Sharp & Dohme Corp. (Consultant, Grant/Research Support) Matthew Sims, MD, PhD, Astra Zeneca (Independent Contractor)Diasorin Molecular (Independent Contractor)Epigenomics Inc (Independent Contractor)Finch (Independent Contractor)Genentech (Independent Contractor)Janssen Pharmaceuticals NV (Independent Contractor)Kinevant Sciences gmBH (Independent Contractor)Leonard-Meron Biosciences (Independent Contractor)Merck and Co (Independent Contractor)OpGen (Independent Contractor)Prenosis (Independent Contractor)Regeneron Pharmaceuticals Inc (Independent Contractor)Seres Therapeutics Inc (Independent Contractor)Shire (Independent Contractor)Summit Therapeutics (Independent Contractor)